THE FINANCIAL CONDITIONS DIVERSIFICATION IN CZŁUCHOWSKI DISTRICT COMMUNITIES IN THE YEARS 2013-2017 (Research Bulletins of the Faculty of Economic Sciences, 2019)
The aim of the article is to assess the level of financial condition of the communes of the Człuchów poviat in 2013-2017. The budget indicators and indices of liabilities for municipalities from the data of the Ministry of Finance were used in the work. The level of financial condition was determined using the non-standard method of the synthetic index based on the average values (from 2013-2017) of the above-mentioned indicators. It has been proven that the level of financial condition depends on its strategy and specificity, and is not dependent on its type.
Keywords: financial condition, commune, budget and liabilities indicators